Espumantes de maçã obtidos pelos processos ASTI, Charmat e Champenoise - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
The use of musts made with apples discarded during classification to in natura trade and the artificial gasification of the fermented, undertake the quality of Brazilian cider. The fermentation process used results in carbon dioxide loss and, consequently, aromatics compounds with large importance to the sensorial attributes of the fermented as well. The product quality could be improved by the use of selected apples cultivars and by the realization of natural gasification process. The objective of this research was the assessment of sparkling obtained by natural gasification process, by the use of selected apples cultivars. In the sparkling elaboration were used apples of Catarina, Granny Smith and Pink Lady cultivars (2007/2008 crop), which were selected because they present physic-chemical characteristics suitable to the process. Six varietal sparklings were elaborated, all by the Champenoise method, and four mixture sparklings, elaborated from a must made by a mixture of the three cultivars, in which the proportions were defined by a statistic planning. The mixture sparklings were elaborated by four different methods: process Chempenoise, artificial gasification, Asti and Charmat, being the two last made in pilot scale. All sparklings were evaluated by physic-chemical and chromatographic analysis, as well as oenology tasting, being classified by the Principal Compounds Analysis (PCA) statistical method. The PCA use, besides the results obtained by the oenology tasting, allowed the varietal sparklings to be classified in groups made by the apple cultivar used in the elaboration and by the glucose source used in the supplementation of the base-fermented. In this way, was evidenced the significant difference between them and, therefore, the need of elaboration of a mixture so that the characteristics of each cultivar would be demonstrated in a unique must. The use of statistic planning allowed the formulation of mixture must with physic-chemical characteristics adapted to the sparkling elaboration, with were evaluated and compared to a commercial apple sparkling made in Switzerland by the Champenoise method. In the oenology tasting, in all the resultant sparklings was identify the lack of freshness and limpidity, indicating the need of the use of apples with higher acidity and more effective filtration processess. The differentiation between the varietal, mixture and commercial sparkling was possible by the use of PCA, on which the chromatographic parameters were the mainly responsible by the differentiation between the varietal and mixture groups, whilst the physic-chemical parameters, specially acidity and turbidity, were the mainly responsible by the isolation of the commercial sparkling in a third group. It wasn’t evidenced significant difference between the elaboration process. The use of natural gasification process and musts elaborated by mixture of selected apple cultivars were promising measures in the obtention of quality natural apple sparklings.
Espumantes de maçã obtidos pelos processos ASTI, Charmat e Champenoise
Keywords: Catarina; Granny Smith; Pink Lady; mistura; estatística; espumante; Catarina; Granny Smith; Pink Lady; mixture; statistic; sparkling; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS